2011
DOI: 10.1016/s0140-6736(11)60278-x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of early treatment with tranexamic acid in bleeding trauma patients: an exploratory analysis of the CRASH-2 randomised controlled trial

Abstract: The importance of early treatment with tranexamic acid in bleeding trauma patients: an exploratory analysis of the CRASH-2 randomised controlled trialThe CRASH-2 collaborators* SummaryBackground The aim of the CRASH-2 trial was to assess the eff ects of early administration of tranexamic acid on death, vascular occlusive events, and blood transfusion in trauma patients with signifi cant haemorrhage. Tranexamic acid signifi cantly reduced all-cause mortality. Because tranexamic acid is thought to exert its eff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
238
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 895 publications
(247 citation statements)
references
References 13 publications
5
238
1
3
Order By: Relevance
“…Antifibrinolytic drugs are used worldwide to decrease the requirement for blood transfusions, reduce the risk of reoperation for bleeding, and lower mortality associated with hemorrhage following major trauma 1, 2, 3. The most commonly used antifibrinolytic drugs include tranexamic acid (TXA), ɛ‐aminocaproic acid (EACA), and aprotinin 1.…”
mentioning
confidence: 99%
“…Antifibrinolytic drugs are used worldwide to decrease the requirement for blood transfusions, reduce the risk of reoperation for bleeding, and lower mortality associated with hemorrhage following major trauma 1, 2, 3. The most commonly used antifibrinolytic drugs include tranexamic acid (TXA), ɛ‐aminocaproic acid (EACA), and aprotinin 1.…”
mentioning
confidence: 99%
“…14 If tranexamic acid is effective after traumatic brain injury, it should also be most effective when given soon after injury, when intracranial bleeding is ongoing. 8 The potential for harm also exists however.…”
mentioning
confidence: 99%
“…However, whilst the trial was underway, new research suggested a shorter therapeutic window than 8 hours 12, 13 . The new data showed that tranexamic acid is most likely to improve outcome if given soon after injury and would be unlikely to improve outcome if given beyond three hours of injury.…”
Section: Trial Methodsmentioning
confidence: 99%
“…This was based on the CRASH-2 trial results which showed that giving tranexamic acid to patients with traumatic extra-cranial bleeding within eight hours of injury reduces death due to bleeding and all-cause mortality 11 . However, pre-specified subgroup analyses showed that the effect of tranexamic acid depends on the time interval between the injury and start of treatment 12 . Treatment within three hours of injury substantially reduced death due to bleeding and all-cause mortality whereas treatment started after three hours appeared to increase death due to bleeding and had no effect on all-cause mortality.…”
Section: Statistical Analysis Planmentioning
confidence: 99%
See 1 more Smart Citation